Analysis of a Frame-Shear Wall Concrete Structure by Using Base Isolation and Evaluation of Structure-Soil Interaction - Polat, H. I. (Engineering, Technology & Applied Science Research, 2017)
A base isolation system is a type of earthquake-resistant structure design approach based on the principle of reducing a structure’s earthquake response rather than increasing the structure’s earthquake resistance capacity. Seismic base isolated structures have the ability to make large displacements relative to the level of insulation elements. This means that a large structure performs very small displacements between floors during an earthquake and exhibits a rigid body behavior. At this point, the earthquake forces acting on the structure decrease along with the floors. In this article a school building composed of frame-shear wall is resolved primarily with the traditional fixed base structure system, mode shapes are found and periods are obtained. For earthquake response analysis, earthquake loads are distributed to the floors using the equivalent seismic load method and structural elements experiencing capacity problems are found. Then, using the earthquake record, larger failure of cross sections and capacity problems are obtained compared to the first method. In the second stage, the same structure is dissolved again by placing the lead core rubber base isolators between the base and the vertical structural members. The periods of structures under earthquake load have increased significantly by utilizing base isolation, as a result of that spectral accelerations decreased. Thus, large decreases in the shear forces acting to the structure are determined and failures of cross sections are removed.